2017
DOI: 10.1051/matecconf/201712009007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban expansion on potential flooding, storage and water harvesting in the city of Sharjah, United Arab Emirates

Abstract: Abstract. The work presented in this article is an extension of an earlier study [1] in which runoff in the city of Sharjah, United Arab Emirates (UAE), was assessed for the period 1967-2010. In this study, the impacts of urban expansion on potential flooding, storage and water harvesting were assessed for the period 1976-2016 using rainfall data recorded during the same period. Sharjah is a generally a flat coastal city that is located in a dry hot region average rainfall of approximately 100 mm/y. Remote sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Shanableh et al [22] studied the impact of urban expansion on urban flooding and water harvesting in Sharjah. The study confirmed that the four-time increase in built-up areas coincided with a ten-fold increase in population growth over the same period.…”
Section: Hydrological Issues Associated With Urban Growthmentioning
confidence: 99%
“…Shanableh et al [22] studied the impact of urban expansion on urban flooding and water harvesting in Sharjah. The study confirmed that the four-time increase in built-up areas coincided with a ten-fold increase in population growth over the same period.…”
Section: Hydrological Issues Associated With Urban Growthmentioning
confidence: 99%
“…The rapid urbanization of arid regions over the past several decades has not only altered the surface hydrology but has also changed other components of the water cycle (e.g., Salvadore [11], In the UAE, the conversion of pervious desert soils to expansive areas of impervious cover, through rapid urbanization, has drastically increased runoff and rerouted natural channels [9]. Sandy soils of high infiltration capacity have been replaced by asphalt and concrete surfaces which allow for little natural mitigation to precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…Most flooding in the UAE occurs during the rainy season from October to March, especially in the northern and eastern coastal watersheds [9]. For example, heavy downpour in October and November 2017 resulted in flash flooding in Al Fujairah and Al Sharjah leading to street and wadi flooding that swept away cars and caused fatalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the knowledge of the current authors, there are no comprehensive studies in the literature investigating the urbanization effects on floods for Sharjah city. Although Shanableh and Al-Ruzouq [19] and Shanableh et al [20] investigated land cover change and urbanization in Sharjah city, neither of these studies focused on the urbanization and flood relationship. In the current study, first, the temporal and spatial variation of land cover change and associated impacts on runoff were assessed using satellite images coupled with a geographic information system (GIS) over the period from 1976-2016.…”
Section: Introductionmentioning
confidence: 99%